Heliospheric Current Sheet Crossings Observed by Voyager 2 across 1–33.6 au - Dooyoung Choi; Dae-Young Lee (The Astrophysical Journal, 2025)
In this study, we identified 188 heliospheric current sheet (HCS) crossing events observed by Voyager 2 between 1977 and 1990, spanning heliocentric distances from 1 to 33.6 au. The identified HCS crossings revealed well-defined trends including a >30% decrease in magnetic field intensity and >20% increases in proton density and temperature. The Harris sheet model fitting to all 188 HCS crossing events indicates that the estimated HCS thickness spans over 2 orders of magnitude, ranging from $7\times {10}^{3}$ to $2.5\times {10}^{6}$ km, with a median value of $3.3\times {10}^{5}$ km. For 84.6% of the events, the HCS planes lie within $-30^\circ $ to $30^\circ $ in latitude from the equatorial plane, whereas the others indicate highly tilted HCS planes. Similarly, for 85.6% of the events, the HCS planes align with the Parker spiral field from the Parker field direction (within 30°), whereas the others exhibit significant longitudinal tilt. Additionally, a substantial fraction of HCS crossings indicate a significant normal magnetic field component (e.g., ${B}_{\mathrm{normal}}/\left|B\right|\,\gt $ 0.3 for 38.8% of the total events), implying rotational discontinuities. Comparing our results with previous studies on HCS thickness from near the Sun to the heliosheath, we find a general increase in thickness with distance. Notably, at 1–33.6 au, HCS thickness remains significantly larger than the ion inertial length, implying conditions generally unfavorable for magnetic reconnection. This contrasts with recent reports of frequent reconnection at HCSs closer to the Sun. Our findings provide a comprehensive insight into the HCS structures across a wide range of heliospheric distances.